Representations of Transsexuality in the Czech Medical Discourse and Documentary Films After 1989 - Jahodová, Dita (Dějiny – teorie – kritika, 2011)
This contribution maps the ways in which transsexuality has been defined in the context of Czech medical discourse from 1989 to the present and the ways in which transsexuality has been represented and self-represented in the Czech documentary films of that era. The purpose of this text is to point out the still predominant power and limits of the medical conceptualization of transsexuality from a gendered perspective, and to introduce a certain queer approach to transsexuality and transpeople. From the analysis we can see that the representation of transsexuality in Czech documentary films reproduced, to a marked degree, the medical perception of transsexuality founded on biodeterministic connection of sex and the dichotomy of man/woman, heterosexual/homosexual, and contributed to the naturalization of transpeople’s perceived otherness. Transpeople’s acceptance of the medical conceptualization of transsexuality, however, does not necessarily implicate submission (or belief ) in the dominant medical discourse but can be a strategy for the transsexual to legitimize their identity in a heteronormative environment.